ANALISIS KEUNTUNGAN PENGRAJIN SAPU IJUK DI DESA SIA KELURAHAN KOTAMOBAGU UTARA (Profit Analysis of Palm Fiber Broom Craftsman in Sia Village, North Kotamobagu) - Indri Ester Maramis; Gene H. M. Kapantow; Grace Adonia Josefina Rumagit (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aims to analyze the business profit of Palm Fiber Broom Craftmen in Sia Village, Kotamobagu Utara Village. This research was conducted for three months, from December 2020 to February 2021. The saturated sampling method (census) was applied in this study by taking all members of the population of the palm fiber broom craftsmen in Sia Village, namely 10 people, as respondents. The data used in this study were primary and secondary data. Primary data were obtained through direct interviews with the craftsmen using a list of questions (questionnaire) that had been prepared. Secondary data were obtained from agencies involved in this study. The data analysis used in this research is business profit analysis.            The results of this study indicated that the average profit of each palm fiber broom craftsman in Sia Village, Kotamobagu Utara Village was IDR 910,413.90 / month, with a value of R / C ratio was 1.34.